Study of the sign change of exchange bias across the spin reorientation transition in Co(Cr1−xFex)2O4 (x = 0.00–0.125). (2nd December 2016) - Padam, R; Pandya, Swati; Ravi, S; Ramakrishnan, S; Nigam, A K; Grover, A K; Pal, D
Abstract: We present the evolution of novel phenomena of magnetic compensation effect, exchange bias (EB) effect and the field induced anomalies in ' F e ' substituted multiferroic compound C o C r 2 O 4 . A few percent of ' F e ' substitution for ' C r ' in C o C r 2 O 4 results in the reversal of field cooled magnetization under low applied fields below compensation temperature T comp . Further, increase in the field leads to the spin reorientation transition ( T SR ). Signature of EB in a narrow temperature window in the vicinity of T SR and its sign change across T SR is observed. Magnitude of EB depends on the amount of compensation and rigidity of the spin reorientation. We also notice the appearance of positive EB below the lock-in transition ( T L ). Presence of unidirectional anisotropy developed in the commensurate spin-spiral below T L could be responsible for the appearance of EB below T L .